A Case of Accidental Formic Acid Poisoning - Sushil Kiran Kunder, A. Avinash, Sharath Madhyastha, Raviraj Acharya, Vinaya Gopalaswamy, Girisha Balaraju, Navin Patil, Amod Tilak (Journal of Applied Pharmaceutical Science, 2016)
Formic acid is a commonly available compound, available commercially for the purpose of coagulating rubber. It is a highly corrosive agent. Consumption of this pungent liquid has resulted in dire consequences, based on the available literature. There have been a few reports of accidental/suicidal consumption of formic acid in the past. This is one such case report of an accidental poisoning with formic acid, with successful management and recovery.
Keywords: Rubber, Corrosive, Gastrointestinal bleed, Caustic.